Young consumers’ perceptions of and preferences for alternative meats: an empirical study in Japan and China - Huang, Shuo; Uehara, Takuro (Frontiers in Sustainable Food Systems, 2023)
Introduction Alternative meats have the potential to shape a sustainable food system. This study examined young consumers’ perceptions of and preferences for plant-based and cultured meats. Since comparative studies on consumer preferences for alternative meats in different key Asian markets remain insufficient, this study was conducted in Japan and China, both of whom have promising alternative meat markets in Asia. Methods We conducted a discrete choice experiment and co-occurrence networks among 2006 (n = 887 in Japan and n = 1,119 in China) young consumers. This study adopted a treatment-control design where respondents in the treatment groups received health information on the use of antibiotics in meat production. Results Respondents in both countries perceived meat alternatives to be substitutes to conventional meat and associated them with plant-based proteins, processed products, and health benefits. In general, Japanese and Chinese respondents differed in their preferences for burger patties but had similar preferences for other attributes. Respondents in both countries were willing to pay a premium for “antibiotic-free,” “traceable,” and low carbon footprint labeling. This study reveals the heterogeneity of consumer preferences and the complexity of the impact of information interventions on consumer preferences. Discussion Plant-based meat is already available on the market in both countries, whereas cultured meat is still in the research and development stage. Hence, young consumers were more familiar with plant-based meat than cultured meat. It is worth noting that young Japanese consumers preferred cultured meat to conventional meat. This is attributed to the concerns about food security and food animal welfare. Furthermore, this study found that information intervention can induce and direct respondents’ attention to an aspect of alternative meats that is negatively perceived. Based on the findings, this study has three implications for promoting alternative meat products: marketing messaging, food labeling, and product development.